HUBUNGAN POLA HIDUP SEHAT, JENIS KELAMIN DAN UMUR DENGAN FAKTOR RESIKO TERJADINYA PENINGKATAN KADAR GULA DARAH - Bernarda Teting; Yani Yani (Poltekkes Kemenkes Kalimantan Timur, 2019)
A healthy lifestyle is a need that cannot be abandoned by everyone. This is due to the increasing number of new diseases that emerge as a result of the wrong lifestyle. The study aimed to determine the relationship between healthy sex life patterns, age with risk factors for increasing blood sugar levels in Pasundan Health Center (Puskesmas). The research method is cross sectional. This study was analyzed by univariate, bivariate, and multivariate. Based on the formulation of the problem, the conclusions of this study are: 1. The healthy lifestyle of the respondents is categorized as not good. 2. The respondent's blood sugar levels are classified as high. 20% belong to the normal category, 62.4% have diabetes mellitus status, and 18.4% are categorized as dangerous. 3. The influence of sex on blood sugar levels is not significant, the effect of age on blood sugar levels is significant in bivariate analysis, but not significant in multivariate analysis, the effect of a healthy lifestyle on blood sugar levels is significant in both bivariate analysis and multivariate analysis. It is recommended to: a) Maintain a diet and avoid foods that contain flavorings. b) Quit smoking, c) carry out regular routine and control activities.